Meta-analisis: Pengaruh media pembelajaran berbasis teknologi digital terhadap kemampuan berpikir kritis siswa - Noor, Eneng Siti Juariah; Ratnaningsih, Nani; Rahayu, Diar Veni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This study aims to analyze a collection of previous research through a meta-analysis that investigates the effect of using digital-based learning media on students' critical thinking skills. This analysis is important because many students still exhibit limitations in critical thinking abilities. The articles included were obtained using Publish or Perish 8 with publication years ranging from 2015 to 2025, resulting in 23 data points from 21 selected articles. Several moderator factors considered in this meta-analysis include educational level, year of publication, and source of publication. The results regarding the influence of digital-based learning media on students' critical thinking skills are as follows: (1) there is a significant overall effect with an effect size (ES) of 1.086 (categorized as high); (2) the effect is more effective when used at the elementary school level or equivalent (ES = 1.7396, high category) based on educational level; (3) the influence is greater in the post-COVID-19 period (ES = 1.1504, high category) based on year of publication; and (4) a greater effect is found in articles published in conference proceedings (ES = 1.3627, high category) based on publication source.